2020
DOI: 10.1002/adma.201908242
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Ultrathin 2D Wide‐Bandgap BiOBr Nanoflakes for Gate‐Controlled Deep‐Ultraviolet Phototransistors

Abstract: Ternary two‐dimensional (2D) semiconductors with controllable wide bandgap, high ultraviolet (UV) absorption coefficient, and critical tuning freedom degree of stoichiometry variation have a great application prospect for UV detection. However, as‐reported ternary 2D semiconductors often possess a bandgap below 3.0 eV, which must be further enlarged to achieve comprehensively improved UV, especially deep‐UV (DUV), detection capacity. Herein, sub‐one‐unit‐cell 2D monolayer BiOBr nanoflakes (≈0.57 nm) with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 47 publications
1
84
0
1
Order By: Relevance
“…Figure 4f depicts the normalized photoresponse as a function of the pulsed light frequency, with ≈50 kHz for a 3 dB frequency ( f 3dB : frequency response dropped to 0.707 of its peak value), [ 42 ] which is among the fastest for 2D TMD‐based photodetectors. [ 28,31,43,44 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4f depicts the normalized photoresponse as a function of the pulsed light frequency, with ≈50 kHz for a 3 dB frequency ( f 3dB : frequency response dropped to 0.707 of its peak value), [ 42 ] which is among the fastest for 2D TMD‐based photodetectors. [ 28,31,43,44 ]…”
Section: Figurementioning
confidence: 99%
“…Figure 4f depicts the normalized photoresponse as a function of the pulsed light frequency, with ≈50 kHz for a 3 dB frequency (f 3dB : frequency response dropped to 0.707 of its peak value), [42] which is among the fastest for 2D TMD-based photodetectors. [28,31,43,44] To gain more insight into the operation mechanism, the energy band diagram of the PtTe 2 /Si vertical Schottky junction is illustrated in Figure 5a. Due to the different W F of multilayer PtTe 2 (≈4.80 eV) with n-Si (≈4.25 eV), when the mosaic-like 2D PtTe 2 layer is in contact with Si, a built-in potential will be formed.…”
mentioning
confidence: 99%
“…[ 25 ] Although some studies have shown that the 2D‐hBN‐based deep‐UV detector presents a high on/off ratio of 10 3 , the missing wave range (only less than 210 nm detectable) and low responsivity make it difficult for practical SBPD application. [ 26–30 ] Up to date, several 2D WBSs, such as GaS, [ 31,32 ] Ga 2 In 4 S 9 , [ 33 ] NiPS 3 , [ 34 ] FePS 3 , [ 35 ] and BiOBr, [ 36 ] own intrinsic large bandgap (up to 3.4 eV) showing poor wavelength selectivity in solar‐blind photodetection. Compared with these 2D WBSs, 2D ultrawide bandgap semiconductors (UWBSs), as the next generation of semiconductor materials with bandgaps significantly wider than the 3.4 eV, [ 5 ] are particularly suitable for solar‐blind photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14–21 ] The promising properties of 2D materials include attractive carrier mobility, peculiar excitonic, widely adjustable bandgaps, and light–matter interaction properties. [ 22–27 ] 2D materials have been proposed to be a potential material family for the next‐generation optoelectronic devices such as photodetector (PD), transistors, wearable devices, and ultracompact spintronics drives. [ 28–33 ] Nevertheless, the exploring of novel 2D materials is still important for broadening their applications.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] The promising properties of 2D materials include attractive carrier mobility, peculiar excitonic, widely adjustable bandgaps, and light-matter interaction properties. [22][23][24][25][26][27] 2D materials have been proposed to be a potential material family for the next-generation optoelectronic devices such as…”
Section: Introductionmentioning
confidence: 99%